Penguatan Sumber Daya Manusia Melalui E-Pak di Kelurahan Semarapura Kaja - A. A. Ayu Dewi Larantika; Ni Made Jaya Senastri; I Made Mardika (Postgraduated Community Service Journal, 2022)
The application of information technology as a form of e-government implementation contributes to improving the welfare and progress of society. E-government is better known as a form of public service by an electronic-based government. Besides being intended to provide information openly about government activities, it is also to facilitate the public in obtaining services related to population administration. However, electronic-based public services in Semarapura Kaja Village are not yet optimal. This can be seen from the very few people who use (visit) the site and the complaints of the public in accessing population administration services. The method of activity in this PKM is making an application for managing a residence certificate, socializing and assisting the use of the application. The output of the activity is in the form of an e-PAK application, namely an application for electronic-based village administration as well as assistance for officers and the community to take advantage of these services.